The Impact of E-Banking Services on The Performance of Vietnamese Commercial Banks - Đinh Thi Thu , Hong; Nguyen Huu , Tuan; Tran Thi Hai , Ly (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This paper examines the influence of e-banking growth on the performance of Vietnamese commercial banks. The number of ATMs, POS/EFTPOS/EDC machines, the number of payment cards, the balance of payment card accounts, and the value of card payments are employed to measure the e-banking services. Using fixed-effects ARDL (autoregressive distributive lag) estimator for a balanced panel dataset of 10 selected domestic joint-stock commercial banks in Vietnam in the period of Q1/2013–Q1/2021, the author find that e-banking services have significantly negative effects on commercial banks’ performance. These findings are surprising and seems contrary to common expectations.